2020
DOI: 10.1371/journal.pone.0234324
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood property value and type 2 diabetes mellitus in the Maastricht study: A multilevel study

Abstract: Low individual socioeconomic status (SES) is known to be associated with a higher risk of type 2 diabetes mellitus (T2DM), but the extent to which the local context in which people live may influence T2DM rates remains unclear. This study examines whether living in a low property value neighbourhood is associated with higher rates of T2DM independently of individual SES. Research design and methodsUsing cross-sectional data from the Maastricht Study (2010-2013) and geographical data from Statistics Netherlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The index results are concurrent with the literature, in that higher neighborhood SES and local greenspace exhibit a protective effect [ 2 , 5 , 11 , 12 , 14 , 15 ]. In terms of urban/regional planning policy and diabetes prevention, low SES, unhealthy food environments, and lack of infrastructure for physical activity have been underscored as key priorities [ 1 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The index results are concurrent with the literature, in that higher neighborhood SES and local greenspace exhibit a protective effect [ 2 , 5 , 11 , 12 , 14 , 15 ]. In terms of urban/regional planning policy and diabetes prevention, low SES, unhealthy food environments, and lack of infrastructure for physical activity have been underscored as key priorities [ 1 ].…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have identified a higher prevalence of diabetes in subpopulations with low socioeconomic status (SES), most commonly measured using composite indices that capture diverse aspects of socioeconomic (dis)advantage [ 2 , 3 ]. When measured at the individual- or household-level, socioeconomic risk factors for diabetes include income [ 4 ], educational attainment [ 5 , 6 ], and occupational status [ 5 ]. Individual SES is not distributed randomly, and low and high SES individuals cluster together, which can be measured using area-based SES measures, for example, using census tracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unemployment might lead to chronic stress, anxiety, unhealthy food choices and hence an increased risk of type 2 diabetes 26,27 . Poorer neighbourhoods might have less availability of healthy food options and physical activity amenities, hence an increased risk for obesity and type 2 diabetes 28 …”
Section: Discussionmentioning
confidence: 99%
“…Neighbourhood inequities in anthropometric factors such as overweight and obesity likely contribute to associations between neighbourhood disadvantage, CVD and T2D. Overweight and obesity are strongly associated with these (and other) chronic degenerative conditions [4][5][6][7], and studies conducted in Australia [8,9], North America [10,11], and elsewhere [12,13] indicate that residents of disadvantaged neighbourhoods, particularly women, are more likely to be overweight or obese.…”
Section: Introductionmentioning
confidence: 99%